SUKUM 2015: USM TARGETS ANOTHER EXCELLENT PERFORMANCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 120 athletes from various sports will represent Universiti Sains Malaysia (USM) at the 2015 Malaysian University Staff Sports Championship (SUKUM 2015) beginning from 17 to 23 August at Universiti Teknologi Mara (UiTM) Shah Alam.